International best-practice models for perinatal and infant mental health care – a scoping review - Reinsperger, Inanna; Paul, Jean Lillian; Zechmeister-Koss, Ingrid (Frontiers in Psychiatry, 2025)
BackgroundPerinatal mental illnesses (PMI) affect up to 20% of women and 10% of men during pregnancy and in the first year after the birth of the child. Perinatal mental illness contributes significantly to maternal mortality and adverse neonatal, infant, and child outcomes. Because of the high prevalence and the impact of PMI on both the parents and the infant, there is an urgent need for rapid and effective care. The aim of this scoping review was to identify comprehensive evidence-based guidelines and care models for the prevention and treatment of PMI and summarize their common characteristics.MethodsWe searched manually in several databases and on websites of relevant institutions and contacted experts. We included guidelines and guidance documents based on pre-defined inclusion criteria.ResultsWe identified six relevant guidelines and care models from four countries (United Kingdom, Ireland, Canada, Australia). The identified documents highlight the need for integrated care models (including prevention, early identification, counseling, treatment), clear referral pathways, stepped-care approaches and multi-professional, coordinated networks.ConclusionsThe ‘ideal’ care model should consider not only the mental health of the mother, but also that of the father/co-parent and the children, as well as the parent-infant relationship. The results from this scoping review can be used for further discussion and as decision support for designing, developing, and implementing perinatal and infant mental health (PIMH) care.